El banco de Ostrea iridescens (Pterioida: Ostreidae) de Bahía Curú, Costa Rica - Campos M., Jorge A (Universidad de Costa Rica, 1990)
Two natural, non-exploited oyster beds of Ostrea iridescens were idenúfied and studied in Bahía Curú, Golfo de Nicoya, Costa Rica. The Nonhem bed is 81 m in length at its longest axis, and the Soulhem 108 m. The population at both beds was estimated in 144,538, with a mean density of 176/m2 at 7.5 cm (S.D.=2.93 cm). Oysters less than 2 cm in lenglh, found attached to the larger individuals, added to 355,129. Considering the small estimated economic value, protecÚon of the oyster beds is recornmended as sources of natural seed and adults